Restrictive intraoperative fluid optimisation algorithm improves outcomes in patients undergoing pancreaticoduodenectomy: A prospective multicentre randomized controlled trial. - Laurence Weinberg; Damian Ianno; Leonid Churilov; Ian Chao; Nick Scurrah; Clive Rachbuch; Jonathan Banting; Vijaragavan Muralidharan; David Story; Rinaldo Bellomo; Chris Christophi; Mehrdad Nikfarjam (PLoS ONE, 2017)
We aimed to evaluate perioperative outcomes in patients undergoing pancreaticoduodenectomy with or without a cardiac output goal directed therapy (GDT) algorithm. We conducted a multicentre randomised controlled trial in four high volume hepatobiliary-pancreatic surgery centres. We evaluated whether the additional impact of a intraoperative fluid optimisation algorithm would influence the amount of fluid delivered, reduce fluid related complications, and improve length of hospital stay. Fifty-two consecutive adult patients were recruited. The median (IQR) duration of surgery was 8.6 hours (7.1:9.6) in the GDT group vs. 7.8 hours (6.8:9.0) in the usual care group (p = 0.2). Intraoperative fluid balance was 1005mL (475:1873) in the GDT group vs. 3300mL (2474:3874) in the usual care group (p<0.0001). Total volume of fluid administered intraoperatively was also lower in the GDT group: 2050mL (1313:2700) vs. 4088mL (3400:4525), p<0.0001 and vasoactive medications were used more frequently. There were no significant differences in proportions of patients experiencing overall complications (p = 0.179); however, fewer complications occurred in the GDT group: 44 vs. 92 (Incidence Rate Ratio: 0.41; 95%CI 0.24 to 0.69, p = 0.001). Median (IQR) length of hospital stay was 9.5 days (IQR: 7.0, 14.3) in the GDT vs. 12.5 days in the usual care group (IQR: 9.0, 22.3) for an Incidence Rate Ratio 0.64 (95% CI 0.48 to 0.85, p = 0.002). In conclusion, using a surgery-specific, patient-specific goal directed restrictive fluid therapy algorithm in this cohort of patients, can justify using enough fluid without causing oedema, yet as little fluid as possible without causing hypovolaemia i.e. "precision" fluid therapy. Our findings support the use of a perioperative haemodynamic optimization plan that prioritizes preservation of cardiac output and organ perfusion pressure by judicious use of fluid therapy, rational use of vasoactive drugs and timely application of inotropic drugs. They also suggest the need for further larger studies to confirm its findings.